Case Report: Case Series of Children With Multisystem Inflammatory Syndrome Following SARS-CoV-2 Infection in Switzerland - Fouriki, Athina; Fougère, Yves; De Camaret, Caroline; Blanchard Rohner, Géraldine; Grazioli, Serge; Wagner, Noémie; Relly, Christa; Pachlopnik Schmid, Jana; Trück, Johannes; Kottanatu, Lisa; Perez, Estefania; Perez, Marie-Helene; et al. (Frontiers in Pediatrics, 2021)
Since the beginning of the severe SARS-CoV-2 pandemic, an increasing number of countries reported cases of a systemic hyperinflammatory condition defined as multi-system inflammatory syndrome in children (MIS-C). The clinical features of MIS-C can be an overlap of Kawasaki Disease (KD), Toxic Shock Syndrome (TSS), Macrophage Activation Syndrome (MAS) or have often an acute abdominal presentation. Intravenous immunoglobulin (IVIG) is recommended as first line therapy in KD. Recent evidence suggests intravenous immunoglobulins (IVIG) resistance in some cases of SARS-CoV-2 related MIS-C, thereby questioning the benefit of immunomodulators such as IL-1 or IL-6 blocking agents. We report on a cohort of 6 Swiss children with SARS-CoV2 related MIS-C presenting with clinical features compatible with Incomplete KD and Toxic Shock Syndrome associated to a cytokine storm. Serum cytokine profile investigations showed increased IL1RA levels (8 to 22-fold) in 5 of the 6 patients (one patient had not been tested), whereas IL-6 serum levels were increased only in the 3 patients of the 6 who were tested. With exception of one patient who had only benefited by Anakinra, all patients received at least one dose of IVIG. One patient has only received Anakinra with favorable evolution, and three patients had also a steroid treatment. In addition to all this anti-inflammatory medication two patients have also received one dose of anti-IL6. In conclusion, our case series reports on clinical and laboratory findings of most of Swiss cases with MIS-C and suggests the use of Anakinra as an alternative to steroids in these children, most of whom presented with high IL-1RA levels.